Trained Innate Immunity of Fish Is a Viable Approach in Larval Aquaculture - Zhang, Zuobing; Chi, Heng; Dalmo, Roy A. (Frontiers in Immunology, 2019)
The general understanding has been that only adaptive immunity is capable of immunological memory, but this concept has been challenged in recent years by studies showing that innate immune systems can mount resistance to reinfection - as the innate immune system can adapt its function following an insult. Innate immune training offers an attractive approach in intensive fish larval rearing, especially since the adaptive immune system is not fully developed. Trained innate immunity will potentially favor robust fish in terms of resistance to viral and bacterial diseases. So-called immunostimulants such as ß-glucans have for decades been used both in laboratories and in intensive fish aquaculture. Treatment of fish by ß-glucans (and by other substances with pathogen-associated molecular patterns) often induces activation of non-specific/innate immune mechanisms and induces higher disease resistance. The reported effects of e.g. ß-glucans fit nicely into the concept “trained innate immunity”, but the research on fish does not yet include analysis of epigenetic changes that may be a prerequisite for long-lasting trained innate immunity. In this “perspective”, we will discuss how in practical terms and based on prior knowledge one can introduce innate immune training in brood stock fish, and their offspring, and whether innate immune training by ß-glucans is a viable approach in larval aquaculture.